Ethical Dimension of Public Service - Bambang Kusbandrijo; Ni Putu Tirka Widanti (Iapa Proceedings Conference, 2019)
The concept of New Public Service emphasizes on that government is responsible to provide fast, easy and inexpensive service to the people as citizen. So far, Government of Indonesia has not been able to provide this service even many services are marked by corruption. Mentality of being served than providing service is still massive. It is because low moral culture of the Civil servants to serve and expert professionalism as civil servant. The low moral quality and professionalism of the Civil Servant cause the service in Indonesia is still complicated and takes long time. This weakness becomes the opportunity for corruption. The right training and recruitment process could minimize corruption potency in law enforcement. Through this training, besides improving individual and institutional moral, it also improved the service competence as required in the context of present public administration.